Ga2O3/Si and Al2O3/Si Room-Temperature Wafer Bonding Using in-Situ Deposited Si Thin Film. (20th July 2018) - Takagi, Hideki; Kurashima, Yuichi; Matsumae, Takashi; Ito, Toshimitsu; Watanabe, Hideyuki; Umezawa, Hitoshi; Ohmagari, Shinya
Abstract : Room temperature bonding of Ga2 O3 /Si, Al2 O3 /Si and SiO2 /Si using in-situ deposition of Si films on the oxide materials was investigated. The in-situ deposition process can be performed by standard bonding apparatus for the surface activated bonding using Ar fast atom beam without modification. All of oxide materials were successfully bonded to Si wafers. Minimum thickness of the deposited Si film for successful bonding depends on the oxide materials. SiO2 requires thicker deposited film than the other oxides.